Impact of complete vaccination againts COVID-19 on lethality and deaths per million habitants in Africa 06/05/2022 - Mora-Alvarado, Darner A. (2023)
This study analysed the impact of complete vaccination -with two doses- against COVID-19 in the African countries up to 05/06/2022, specifically with mortality rates per million inhabitants and general lethality, applying Pearson’s linear correlation at 95% between the variable of the percentage of the population with complete vaccination and mortality from Covid-19. The results indicated that Africa, is the continent least affected by Covid-19. The most affected African countries are South Africa (101.317 deaths), followed by Tunisia (28.841 deaths), Egypt (24,719 deaths) and Morocco (16,076 deaths) respectively. However, the nations with the highest fatality rates are Sudan (7,93%), Somalia (5,12%), Egypt (4,79%), Liberia (3,94%) and Niger (3,43%). Linear correlation analysed at 95% indicated an inverse association of 0.24 between complete vaccination and case-fatality rates, but r=0.55 with deaths/million inhabitants, this variable is affected because of the size of each country. The advances in complete vaccination againts Covid-19 in Africa place this continent with less access to vaccines with 23% on average, which shows a great inequality, causing the appearance of new variants of the SARS-CoV-2.